International Prosecution of Macro-Crimes Committed During the Third Artsakh War - Petrossian, Gurgen (Scientific Artsakh, 2021)
This article articulates the possible legal paths open to international criminal law in order to activate the prosecution of macro-crimes committed during the Third Artsakh War. Neither the Republic of Armenia nor Republic of Azerbaijan nor the Republic of Artsakh is not a member of the Rome Statute of the International Criminal Court (ICC). This makes it difficult to initiate the prosecution of war crimes on an international level. The following article highlights the difficulties and alternatives in overcoming the legal obstacles for activating international criminal prosecution, by waging and comparing the possible instruments. The legal comparison and the historical overview allow considering three different levels for the prosecution of international crimes committed during the Third Artsakh War, where national prosecution based on universal jurisdiction seems to be the most efficient to